ANALISIS PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP PROBABILITAS TERJADINYA FINANCIAL DISTRESS - Maryam Maryam; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2019)
This study aims to examine the effect of corporate governance mechanism to financial distress. The dependent variable of this study is financial distress which is proxied as dummy variable has negative net profit for two consecutive years. The independent variable of this study are managerial ownership, institutional ownership, number of board of commissioner, number of the board of directors, and proportion of independent commissioners. Control variables in this study are liquidity, leverage, and sales margin. Population of this study are manufacturing companies listed in Indonesia Stock Exchange (BEI) in 2015-2017. This study used purposive sampling method and logistic regression as the data analysis. Total samples are 279 companies. The results of analysis showed that the managerial ownership, number of board of commissioner, and number of the board of directors have significant impact on financial distress, while institutional ownership and  proportion of independent commissioners did not significantly affect the financial distress.